An amorphous FeMoS4 nanorod array toward efficient hydrogen evolution electrocatalysis under neutral conditions. Issue 64 (26th July 2017) - Ren, Xiang; Wang, Weiyi; Ge, Ruixiang; Hao, Shuai; Qu, Fengli; Du, Gu; Asiri, Abdullah M.; Wei, Qin; Chen, Liang; Sun, Xuping
Abstract : As a durable catalyst, an FeMoS4 nanorod array on carbon cloth shows high activity for hydrogen evolution in neutral media, achieving a geometrical catalytic current density of 10 mA cm −2 at an overpotential of 204 mV. Abstract : It is highly attractive to develop efficient hydrogen-evolving electrocatalysts under neutral conditions. In this communication, we report an amorphous FeMoS4 nanorod array on carbon cloth (FeMoS4 NRA/CC) prepared by hydrothermal treatment of an FeOOH nanorod array on carbon cloth (FeOOH NRA/CC) in (NH4 )2 MoS4 solution. As a 3D electrode for hydrogen evolution electrocatalysis, this FeMoS4 NRA/CC demonstrates superior catalytic activity and strong long-term electrochemical durability in 1.0 M phosphate buffered saline (pH: 7). It needs an overpotential of 204 mV to drive a geometrical current density of 10 mA cm −2, which is 450 mV less than that for FeOOH NRA/CC. Density functional theory calculations suggest that FeMoS4 has a more favourable hydrogen adsorption free energy than FeOOH.